PENGEMBANGAN MEDIA PEMBELAJARAN BOOKLET PADA MATERI SISTEM KOLOID UNTUK KELAS XI IPA (SMA NEGERI 1 BENAI) - Siti Masrifah; Dwi Putri Musdansi; Jumriana Rahayu Ningsih (Universitas Islam Kuantan Singingi, 2020)
Research on the development of learning media on Booklet aims to explain the feasibility of developing based Booklet on colloid system subjects for class XI Senior High School 1 Benai. This research method is research and development (R&D) with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. Data collection instruments used were through expert material validation sheets, learning media validation sheets, and student response validation sheets. The data analysis technique used is by calculating the validation assessment percentage score. The results showed that the interactive learning media on Booklet that was developed fulfilled the valid categories of by three material experts in the amount of 91.11%, three in the media experts amounted to 86,67% and from linguists 83,36%. This learning media also fulfills a valid category which students can use with 91,40%.